Effects Of Soil Group On The Cost Of Industrial Structures - Dikmen, Seyyit Ümit; Özek, Senem (Turkish Chamber Civil Engineers, Selanik Cad No 19-1, Kizilay, Ankara 06650, Turkey, 2011)
Recent occurrences of major earthquakes have necessitated the introduction of new rules and restrictions in the technical specifications in the whole world as well as in Turkey. In this context, in Turkey the current earthquake specification has been revised and DBYYHY-2007 is published in 2007. In Turkey, in the construction of industrial structures, structural steel, reinforced concrete and prefabricated reinforced concrete systems or a combination of these systems are used as the structural system. In this study, a group of single-story industrial structures having different column spans were selected and individually designed for structural steel, cast in-situ reinforced concrete and prefabricated reinforced concrete materials. In designing each sample structure, the soil groups given in the specification DBYYHY-2007 were taken into consideration and the corresponding costs were calculated. The results obtained were evaluated to compare the costs of different structures.
Keywords: structural cost; earthquake; industrial structures; soil group; yapısal maliyet; deprem; endüstriyel yapılar; toprak grubu